Sexual Risk Behaviors of Sex Workers for HIV / AIDS and STIs in the City of Bamako, Mali - Dohinnon, Collette; Traoré, Fatoumata; Mounkoro, Niani; Musuenge, Beatrice; G. Poda, Ghislain (Journal of Clinical Research In HIV AIDS And Prevention, 2021)
Background: HIV / AIDS affects all social strata and including female sex workers who are a particularly vulnerable group at risk of HIV infection. Objective To assess the risky sexual behavior of female sex workers in Bamako, Mali. Methods This is a quantitative cross-sectional analytical study conducted among 288 female sex workers in the city of Bamako, Mali. This study used a questionnaire to collect information from January to April 2021. Results Out of 288 sex workers, 41% came from neighboring countries (Burkina Faso, Cote d'Ivoire, Mauritania). More than half of the participants had started working as sex workers before the age of 20. More than half of sex workers do not always use a condom. About 32% of female sex workers had previously had anal sex, 20% had experienced group sex, and less than a quarter smoked or drank alcohol before sex. A significant relationship was found between the behavior or practice of sex workers with the following variables: ethnicity (P = 0.04); marital status (P = 0.01); monthly income (P = 0.001), age at first sexual intercourse (P = 0.03); the presence of STDs in the past (P = 0.02), knowledge of HIV status (P = 0.04) and nationality (P = 0.03). Conclusions This study highlights negative risk behaviors of sex workers such as not using condoms consistently, anal sex, alcohol, and smoking. It is therefore important to develop education actions to improve the knowledge, attitude, and practice of sex workers related to HIV/ AIDS in Mali.
Keywords: Sex worker; risky sexual behavior; HIV/AIDS